(untitled) (Eurasian Medical Research Periodical, 2022)
The article is devoted to the rehabilitation of patients with congenital and acquired anomalies and deformities in the maxillofacial region. The results of treatment of 216 patients were analyzed. Retrospectively, the long-term results of treatment for up to 10 years were traced. Based on many years of clinical experience, a comprehensive rehabilitation scheme has been developed and introduced into clinical practice for patients undergoing bone-plastic and bone-reconstructive operations in the maxillofacial region, which allows to obtain good anatomical, functional and aesthetic treatment results. The results of rehabilitation of patients depended on the severity of the disease (one- or two-sided joint lesion), the age of the patient, and the method of surgical treatment, the effectiveness of therapeutic and preventive measures aimed at optimizing the longitudinal growth of the mandible